Pewarisan Sifat Komponen Hasil Padi Gogo (Oryza sativa L.). Inheritance of Yield Component Traits of Upland Rice (Oryza sativa L.). - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
Genetic studies, particularly on the inheritance of yield component traits are very importance in breeding program. The plant material used in this study involved the 1R26, OS4 and Salumpikit varieties along with their Fl and F2 progenies of the IR26/0S4 and lR26/Salumpikit crosses. Those entries were planted in Randomized Block Design with three replications. Power et al. technique was applied to study the mode of inheritance of the genes controlling traits, and potence ratio formula of Griffing was used to asses the gene action. The result of the experiment indicates that in both crosses, yield component traits such as maximum tiller. productive tiller, maturaty (ear emergence), ear lenght, total grain and filled grain number per ear, and plant height were polygenic controlled as reflected by their normal distribution frequency of the F2 population. On the other hand, there were some different gene action between those crosses. Gene controlling productive tiller and ear lenght show similar action, that are complete dominance. Maturaty is also controlled by overdominance genes in both crosses. Total grain and filled grain number per ear, and plant height are controlled by no dominance genes in 1826/Salumpikit cross, but by overdominance genes in I R26/0S4 cross. Finally, maximum tiller is controlled by no dominance genes in JR26/Salumpikit cross, and by partial dominance genes in 1R26/0S4 cross.